Clinical difference between identical twins with sickle cell anemia - Marilia R. Laurentino; Tarcisio Paulo Almeida Filho; Pedro A. Maia Filho; Francisco O. F. Nascimento; Adlene F. Advincula; Clarissa Maria G. Machado; Romelia P G. Lemes
ABSTRACT Sickle cell anemia (SCA) is a genetic disease that causes important clinical manifestations due to chronic hemolysis and vascular occlusion. The aim of this study was to report a rare case of monozygotic twins diagnosed with SCA, presenting a different clinical characteristic. An interview with the patients was carried out and the medical records were consulted. One patient has a history of malleolar ulcer in the left back, while the other does not. Both patients used hydroxyurea at the same dosage. This study shows that SCA presents, in addition to genetic factors, non-genetic factors involved in the severity of the disease and its clinical manifestations. Studies are needed that may contribute to the understanding of the clinical heterogeneity of SCA.